Mapping evidence on postpartum modern family planning service uptake among women in Ethiopia: A scoping review - Cherie, Niguss; Abera, Mulumebet; Tura, Gurmesa (Frontiers in Global Women's Health, 2022)
Background In Ethiopia, different fragmented studies have been conducted to assess the determinants and uptake of postpartum modern family planning services. There is discrepancy and inconsistency among reported studies on postpartum modern family planning service uptake. The scoping review aimed to collect evidence on postnatal birth control service use and supply a chance to spot key ideas and gaps to research, policy revision, and changes in strategies. Methods There were different process steps in this scoping review which included analysis questions, distinctive relevant studies, study choice, charting the information, and eventually collating, summarizing, and reporting the results. A search was conducted through scientific databases like PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Hinari, and Google Scholar. The first outcome of this scoping review was postpartum family planning service uptake after childbirth in Ethiopia. The Preferable Reporting Information in Systematic Review and Meta-Analysis (PRISMA) flow diagram was used to select and summarize the selection procedure of the articles. The information of the chosen studies was sorted using the subsequent categories: authors, year of publication, study location, main study objective, and method employed for information analyses. Results A total of 1,607 records were reclaimed from the database searches and reference list review. A total of 596 articles were identified in PubMed, 375 in CINAHL, 576 in Hinari, and 60 records in Google Scholar. A total of 1,607 literature studies were checked for replication, and 840 records were excluded. The bulk of articles (n = 420) were excluded because they did not focus on postpartum family planning service, and 322 articles were excluded due to study setting discrepancy. The remaining 28 full-text articles were read in full using the preidentified inclusion criteria and included in the scoping review for analysis. Conclusion Generally, this scoping review identified different fragmented and inconsistent research findings on the uptake of postpartum modern family planning in Ethiopia. Almost all studies were observational studies that lack interventional study designs to provide evidence-based interventions to improve postpartum family planning uptake. There is a definite need for further interventional and qualitative research to improve early postpartum family planning service uptake that improves maternal and child health.